The end of all taxation and censorship using blockchain technology - Tanmay Munjal, (International Journal of Scientific Research and Management (IJSRM), 2021)
Large scale censorship and control over the free flow of information on the internet that was already implemented on a large scale in many authoritarian countries in China in the past few decades has started to work its way through the more liberal and western countries including India, US etc. especially in the last decade raising concerns over privacy issues and the possibility of a dystopian future of tyrannical governments empowered by the use of digital surveillance technology to increase their power and make them essentially undefeatable on a level unforeseen in the history of humanity among many great thinkers in our era. In this paper, we wish to outline a method to not only combat but to completely eliminate both the possibility and current usage of all censorship and control over flow of information on the internet, hence heralding an era of free flow of information throughout the world and destroying practically all mind control that tyrannical governments can hold over their people, in essence ending the era of propaganda and tyranny from the face of this earth forever, using blockchain technology.